Nurse's role in the prevention of pressure injuries in patients with COVID-19 in the ICU (Research, Society and Development, 2021)
One of the most common consequences resulting from hospitalization, especially in the ICU sector, is the appearance of skin lesions in patients. Objectives: to analyze the available scientific evidence about the role of nurses in the management of care and the prevention of pressure injuries in the ICU in patients with COVID-19. Methodology: Exploratory, descriptive, with a qualitative approach, through an Integrative Literature Review (RIL). The data search was performed based on the descriptors: “Health Care”, “Coronavirus Infections”, “Nursing”; “Pressure Injury”; "Intensive Care Units", delimiting studies published in the time frame between 2019 and 2021. Data collection was carried out from August to October 2021, in the databases: LILACS, BDENF, SciELO, CAPES PUBMED and BIREME. Results and discussion: They were presented in three thematic categories: 1) impacts on the role of nurses in the prevention of pressure injuries in patients with COVID-19 in the ICU; 2) the length of stay of patients with COVID-19 and lack of supplies and 3) the immunological aspects of the patient hospitalized in the ICU with COVID-19. It is observed that PPL acquired in the ICU is associated with increased morbidity and mortality, and it is considered to be largely avoidable. Conclusion: It is the responsibility of nursing professionals to carry out primarily the assessment of risk factors for triggering PPL in their patients, in order to prevent and recognize them early, developing essential parameters for care linked to the integrity of the patient skin.